2017
DOI: 10.3390/molecules22091471
|View full text |Cite
|
Sign up to set email alerts
|

A New Monoterpene from the Leaves of a Radiation Mutant Cultivar of Perilla frutescens var. crispa with Inhibitory Activity on LPS-Induced NO Production

Abstract: The leaves of Perilla frutescens var. crispa (Lamiaceae)—known as ‘Jureum-soyeop’ or ‘Cha-jo-ki’ in Korean, ‘ZI SU YE’ in Chinese, and ‘Shiso’ in Japan—has been used as a medicinal herb. Recent gamma irradiated mutation breeding on P. frutescens var. crispa in our research group resulted in the development of a new perilla cultivar, P. frutescens var. crispa (cv. Antisperill; PFCA), which has a higher content of isoegomaketone. The leaves of PFCA were extracted by supercritical carbon dioxide (SC-CO2) extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…crispa (cv. Antisperill) mainly comprised three major compounds, namely 9-hydroxy isoegomaketone ( 1 ), isoegomaketone ( 2 ), and peril ketone ( 3 ), as indicted by their HPLC profile (Figure 2), obtained using the established method described in our previous reports [9, 21]. For successfully separating target compounds using CPC, a search for an optimum two-phase solvent system with a suitable partition coefficient ( K ) is required.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…crispa (cv. Antisperill) mainly comprised three major compounds, namely 9-hydroxy isoegomaketone ( 1 ), isoegomaketone ( 2 ), and peril ketone ( 3 ), as indicted by their HPLC profile (Figure 2), obtained using the established method described in our previous reports [9, 21]. For successfully separating target compounds using CPC, a search for an optimum two-phase solvent system with a suitable partition coefficient ( K ) is required.…”
Section: Resultsmentioning
confidence: 99%
“…The preparative separation of compounds 1 and 2 using CCS was first reported in this study, although compound 3 has already been separated by high speed countercurrent chromatography [19]. Compound 1 was isolated as a new compound in our previous study [9], and compound 2 has been reported to be isolated only from Perilla species [7, 22] and its synthesis has been studied [23], but a large-scale isolation of 2 using CCS has not been reported before. Therefore, although the simultaneous separation of 1 and 2 was not possible in this study, the optimized conditions are developed for the rapid and large-scale purification of 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations